Impact of Mobile Health (mHealth) Use by Community Health Workers on the Utilization of Maternity Care in Rural Malawi: A Time Series Analysis - Kachimanga C; Ng’ambi WF; Kazinga D; Ndarama E; Amulele MA; Munyaneza F; Abejirinde IOO; van den Akker T; Kulinkina AV (International Journal of Women's Health)
Chiyembekezo Kachimanga,1,2 Wingston Felix Ng’ambi,3 Doctor Kazinga,1 Enoch Ndarama,4 Mercy Ambogo Amulele,5 Fabien Munyaneza,1 Ibukun-Oluwa O Abejirinde,6,7 Thomas van den Akker,2,8 Alexandra V Kulinkina1,9,10 1Partners in Health Malawi, Neno, Malawi; 2Athena Institute, Vrije Universiteit Amsterdam, Amsterdam, Netherlands; 3Health Economics and Policy Unit, Department of Health Systems and Policy, Kamuzu University of Health Sciences, Lilongwe, Malawi; 4Ministry of Health, Neno, Malawi; 5Medic, Nairobi, Kenya; 6Women College Hospital Institute for Health System Solutions and Virtual Care, Toronto, ON, Canada; 7Dalla Lana School of Public Health, University of Toronto, Toronto, ON, Canada; 8Department of Obstetrics and Gynaecology, Leiden University Medical Center, Leiden, Netherlands; 9Swiss Tropical and Public Health Institute, Allschwil, Switzerland; 10University of Basel, Basel, SwitzerlandCorrespondence: Chiyembekezo Kachimanga, Partners in Health Malawi, Post Office Box 56, Neno, Malawi, Email chembekachimanga@yahoo.co.ukPurpose: Maternal mortality in Malawi is high, with low coverage of maternity care being a contributing factor. To improve maternal health coverage, an Android-based, integrated mobile health (mHealth) app called YendaNafe was introduced to community health workers (CHWs) in the Neno district, rural Malawi. This study evaluates the impact of this app on the uptake of antenatal care (ANC), facility-based births, and postnatal care (PNC), compared to a reference period where CHWs provided the same services without mHealth, using the interrupted time series analysis.Patients and Methods: Using aggregated monthly data and segmented quasi-Poisson regression models, we compared the effects of mHealth on selected maternal health outcomes. The models were adjusted for the COVID-19 pandemic, the occurrence of cyclones, and a cholera epidemic. We analyzed data from six eligible health facilities and their respective catchment areas in which CHWs were using YendaNafe, and compared 12 months before and 12 months after its introduction.Results: The use of YendaNafe was associated with a 22% immediate increase in facility-based births (aIRR 1.22, 95% CI 1.12– 1.33, p< 0.001) but not an immediate increase in new ANC visits (aIRR 1.02,95% CI 0.90– 1.14, p=0.77), ANC in the first trimester (aIRR 1.17, 95% CI 0.95– 1.45 p=0.13), or PNC visits (aIRR 1.03, 95% CI 0.79– 1.36, p=0.81). For long-term effect, YendaNafe was associated with an increase in new ANC visits (aIRR 1.04, 95% CI 1.01– 1.07, p < 0.01) and ANC in the first trimester (aIRR 1.03,95% CI 1.00– 1.07 p=0.046), but not facility-based births (aIRR 1.01, 95% CI 0.99– 1.03, p=0.46) or PNC (aIRR 0.97 95% CI 0.93– 1.01, p=0.14).Conclusion: mHealth shows potential of increasing utilization of new ANC visits, ANC in the first trimester and facility-based births. Further research is needed to understand why mHealth did not have an effect on PNC.Keywords: antenatal care, facility-based births, postnatal care, maternity care